Bibliography of ASEAN-China Relations - Yip, Seong Chun (Book collections on Project MUSE., 2006)
Contains a list of titles in English covering relations between ASEAN and China. Titles cover topics such as bilateral relations, economic relations, finance and investment, the Greater Mekong Subregion, maritime issues and territorial disputes, socio-cultural issues, and trade relations.